PENGEMBANGAN MODEL PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN OBYEK WISATA ALAS KEDATON - I Gusti Ketut Purnaya Ketut Purnaya (Institut Pariwisata dan Bisnis Internasional, 2017)
Alas Kedaton Tourism Object has a unique natural resource and it is potential to be attraction for the tourist to visit it. The development of Alas Kedaton Tourism Object will be running well if the quality of natural resource and humanÂ resources is balance. The quality of human resources is one of the important factor to develop the potency of Alas Kedaton Tourism ObjectÂ to be excellent. When the human resources are qualified, the tourism resource will be better. Local society are the human resources that has to be involved. The involvement of local community will give a positive effect for them. The principle of tourism development which is from the community, by the community, and for the community will influence the life of the community to be better. The purposes of this research will be reach in two steps, they are 1) To know the potency of Alas Kedaton Tourism Object , like its culture variety and its unique social society life but the uttilization is not maximun, 2) To identify the development method of community empowerment in managing Alas Kedaton Tourism Object , which is not maximum. This research is using qualitative method. It is used to get data or descriptive explanation about Alas Kedaton Tourism Object and the its prolem. It is also using descriptive-qualitative analysis technic, internal and external factor analysis, and SWOT analysis. The results of this research are 1) The form of community empowerment in managing Alas Kedaton Tourism Object, 2) The development of community empowerment in managing Alas Kedaton Tourism Object.